2007
DOI: 10.1038/sj.bmt.1705614
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough zygomycosis after voriconazole administration among patients with hematologic malignancies who receive hematopoietic stem-cell transplants or intensive chemotherapy

Abstract: Zygomycosis is increasingly reported as a cause of lifethreatening fungal infections. A higher proportion of cases reported over the last decades have been in cancer patients, with or without hematopoietic stem cell transplantation (HSCT). The new anti-fungal agent voriconazole is a recently identified risk factor for developing zygomycosis. We reviewed the clinical characteristics and outcomes of a large cohort of cancer patients who developed zygomycosis after exposure to voriconazole. Health care profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(156 citation statements)
references
References 21 publications
2
146
3
5
Order By: Relevance
“…In our experience, voriconazole is effective as a primary prophylactic agent and is an improvement over previously published results using low-dose amphotericin B deoxycholate/fluconazole (13% IFD) 5 or L-AmB (9.7% of 51 patients underwent 57 allo-SCT had an IFD, whereas none developed an invasive mold infection), 22 which are similar to the results of Kolve et al 29 who used L-AmB as primary or secondary prophylaxis in children (3.5% IFD in the global series), and van Burik et al 19 who used micafungin only during neutropenic phase (2.5% of IFD). In contrast to the published experience of Trifilio et al, 30 who observed breakthrough fungal infections due to opportunistic molds or yeast, in a retrospective study that also included children, we did not observe any of these results.…”
Section: Discussioncontrasting
confidence: 56%
“…In our experience, voriconazole is effective as a primary prophylactic agent and is an improvement over previously published results using low-dose amphotericin B deoxycholate/fluconazole (13% IFD) 5 or L-AmB (9.7% of 51 patients underwent 57 allo-SCT had an IFD, whereas none developed an invasive mold infection), 22 which are similar to the results of Kolve et al 29 who used L-AmB as primary or secondary prophylaxis in children (3.5% IFD in the global series), and van Burik et al 19 who used micafungin only during neutropenic phase (2.5% of IFD). In contrast to the published experience of Trifilio et al, 30 who observed breakthrough fungal infections due to opportunistic molds or yeast, in a retrospective study that also included children, we did not observe any of these results.…”
Section: Discussioncontrasting
confidence: 56%
“…First, several centers have reported breakthrough IFDs in AL patients treated with posaconazole prophylaxis with difficult-to-treat pathogens such as Scedosporium prolificans, Trichosporon asahii, and Mucorales [13][14][15], similar to that which has been observed with voriconazole prophylaxis [16][17][18]. Furthermore, the number of patients needed to treat with antifungal prophylaxis to prevent one IFD varies significantly between centers based on the background rate of IFD at a particular center, which suggests that the results of antifungal prophylaxis studies in general, and posaconazole in particular, may not be generalizable to all centers-particularly those with relatively low rates of IFD [19].…”
Section: Introductionmentioning
confidence: 93%
“…As with any antimicrobial class of drugs, widespread and prolonged use of triazoles may lead to the emergence of drug-resistant organisms [14]. Several reports have linked voriconazole use to a rising incidence of zygomycosis [15,16]. Moreover, unlike with fluconazole, many clinicians routinely obtain serum levels of these azoles in order to ensure efficacy and minimize toxicity.…”
Section: Chemoprophylaxismentioning
confidence: 99%